1996
DOI: 10.1038/ki.1996.121
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence linking urolithiasis and blood coagulation: Urinary prothrombin fragment 1 is present in stone matrix

Abstract: The fact that organic material is always present and distributed throughout each renal calculus suggests that it may play a role in stone formation. The organic matrix of calcium oxalate (CaOx) crystals freshly generated in urine in vitro contains urinary prothrombin fragment 1 (UPTF1) as the principal protein. In this initial study, matrix was extracted from 12 renal calculi and evaluated for the presence of UPTF1 using Western blotting. UPTF1 was present in all eight stones whose principal component was CaOx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…This is in accordance with recent results reported by Dussol et al [8], who found that albumin was the major component of five different morphological types of stones. Furthermore, in a recent paper from Ryall's group [18], the analysis of the organic matrix of kidney stones analyzed by SDS-PAGE showed an intense band at 67 kD corresponding to albumin. Therefore, the conditions used in our experiments may closely reflect those occurring in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with recent results reported by Dussol et al [8], who found that albumin was the major component of five different morphological types of stones. Furthermore, in a recent paper from Ryall's group [18], the analysis of the organic matrix of kidney stones analyzed by SDS-PAGE showed an intense band at 67 kD corresponding to albumin. Therefore, the conditions used in our experiments may closely reflect those occurring in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results and the molecular weight of 28 kDa derived by SDS-PAGE in the unreduced condition, the protein detected here is probably PTF1. Recently, Stapleton et al [27] found PTF1 in calcium phosphate crystals generated in urine, and in the stone matrix of CaOx and calcium phosphate [27]. Urinary PTF1 strongly inhibits CaOx crystal aggregation; therefore its abundance in urine is believed to prevent urinary stone formation [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…This 31-kD protein, which is present in CaOx crystals and in the stone matrix of CaOx and calcium phosphate (CaP) stones [21], has been localized in the thick ascending Henle's loop and in the distal convoluted tubule [22]. This glycoprotein possesses the domain rich in Gla of the native protein which confers the ability to bind calcium ions, thus explaining its inhibitory effect on CaOx crystal aggregation.…”
Section: Crystal Matrix Proteinmentioning
confidence: 99%
“…Described in 1995 by Stapelton and Ryall [21], the formerly called crystal matrix protein is actually a urinary form of prothrombin fragment 1 (F1), a degradation product of prothrombin, the serum zymogen involved in the coagulation. This 31-kD protein, which is present in CaOx crystals and in the stone matrix of CaOx and calcium phosphate (CaP) stones [21], has been localized in the thick ascending Henle's loop and in the distal convoluted tubule [22].…”
Section: Crystal Matrix Proteinmentioning
confidence: 99%